Drug-Coated Balloons versus Everolimus-Eluting Stents in Patients with In-Stent Restenosis: A Pair-Wise Meta-Analysis of Randomized Trials - Nina Peng; Wei Liu; Zongzhuang Li; Jun Wei; Xuejun Chen; Wei Wang; Hao Lin (Hindawi-Wiley, 2020)
Objective. This study aimed to compare the effectiveness of drug-coated balloons (DCB) with everolimus-eluting stents (EES) in the treatment of in-stent restenosis (ISR) and the differential relative effect of DCB in patients with drug-eluting stents (DES)-ISR and bare metal stents (BMS)-ISR. Background. The efficiency and safety of DCB and EES need to be assessed for the treatment of ISR. Methods. A systematic literature search was conducted using PubMed and EMBASE to identify all relevant studies. Angiographic results and clinical events were separately assessed. Subgroup meta-analyses were performed according to the type of restenosed stent. Results. Six randomized trials with 1134 patients were included. The overall pooled outcomes indicated that DCB was associated with lower minimum lumen diameter (mean difference MD=−0.17, 95% CI = −0.29 to −0.05, P=0.006) and higher target lesion revascularization (risk ratio RR=2.38, 95% CI = 1.36 to 4.18, P=0.002) than EES. However, the subgroup meta-analyses showed that DCB was inferior to EES only in DES-ISR patients, with lower minimum lumen diameter (MD=−0.25, 95% CI = −0.37 to −0.14, P<0.001), higher percent diameter stenosis (MD=5.37, 95% CI = 1.33 to 9.42, P=0.009), more binary restenosis (RR=2.07, 95% CI = 1.20 to 3.58, P=0.009), and higher incidence of target vessel revascularization (RR=2.07, 95% CI = 1.22 to 3.50, P=0.007) and target lesion revascularization (RR=2.43, 95% CI = 1.28 to 4.22, P=0.002). No differences in angiographic results and clinical events were found between DCB and EES in BMS-ISR patients. Conclusions. DCB was inferior to EES in DES-ISR and comparable in BMS-ISR in terms of angiographic results and clinical events.